2016
DOI: 10.3747/co.23.2803
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Comparison of Cancer Drug Approvals at Three International Regulatory Agencies

Abstract: BackgroundThe primary objective of the present study was to examine the drug approval process and the time to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The mean time from cancer medicine application at the FDA to submission at the European Medicines Agency or Health Canada was 12.9 months and 28.4 months, respectively . After regulatory approval by the European Medicines Agency or the FDA, it can take ≥1 year for a cancer medicine to be registered in low‐income and middle‐income countries .…”
Section: Optimizing Cancer Medicine Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean time from cancer medicine application at the FDA to submission at the European Medicines Agency or Health Canada was 12.9 months and 28.4 months, respectively . After regulatory approval by the European Medicines Agency or the FDA, it can take ≥1 year for a cancer medicine to be registered in low‐income and middle‐income countries .…”
Section: Optimizing Cancer Medicine Regulationmentioning
confidence: 99%
“…The approval was based on data from 149 patients with unresectable or metastatic, MSI-H or dMMR cancer (84% colorectal, 53% other tumors) across 5 trials; further trials are to be conducted to evaluate response and duration, and it is likely that these will select patients on the basis of MSI-H or dMMR biomarkers VOLUME 70 | NUMBER 2 | MARCH/APRIL 2020 Canada was 12.9 months and 28.4 months, respectively. 95 After regulatory approval by the European Medicines Agency or the FDA, it can take ≥1 year for a cancer medicine to be registered in low-income and middle-income countries. 96 The process for registering cancer medicines in low-income and middle-income countries is complex, inefficient, and costly.…”
Section: Nonrandomized Trials Using Historical Controlsmentioning
confidence: 99%
“…Efforts to pursue harmonisation of drug regulation have been ongoing but differences in the approval characteristics of drugs by different agencies still persist 2. The speed of the regulatory review and approval processes between the major regulators, primarily the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA), have been analysed as a measure of the (dis)alignment of the agencies’ various approval models 3–10…”
Section: Introductionmentioning
confidence: 99%
“…When trials have shown the effectiveness or clinical benefit of a specific treatment, the treatment needs to be approved before it can be implemented and used in clinical practice. Several international regulatory agencies are responsible for these drug approval processes, such as the European Medicines Agency (EMA) and the Food and Drug Administration [ 3 ]. In addition, national bodies typically apply country specific regulations concerning drug approval.…”
Section: Introductionmentioning
confidence: 99%